Access to Vaccination for Newly Arrived Migrants: Developing a General Conceptual Framework for Understanding How to Improve Vaccination Coverage in European Countries - Salvatore Scarso; Salvatore Scarso; Salvatore Scarso; Giulia Marchetti; Giulia Marchetti; Maria Laura Russo; Maria Laura Russo; Franca D'Angelo; Maria Elena Tosti; Arianna Bellini; Chiara De Marchi; Caterina Ferrari; et al. (Frontiers Media S.A., 2023)
Objectives: Access to vaccination for newly arrived migrants (NAMs) is a relevant concern that requires urgent attention in EU/EEA countries. This study aimed to develop a General Conceptual Framework (GCF) for understanding how to improve vaccination coverage for NAMs, by characterizing and critically analyzing system barriers and possible strategies to increase vaccination.Methods: A theoretical conceptualization of the GCF was hypothesized based on conceptual hubs in the immunization process. Barriers and solutions were identified through a non-systematic desktop literature review and qualitative research. The GCF guided the activities and facilitated the integration of results, thereby enriching the GCF with content.Results: The study explores the vaccination of NAMs and proposes strategies to overcome barriers in their vaccination process. It introduces a framework called GCF, which consists of five interconnected steps: entitlement, reachability, adherence, achievement, and evaluation of vaccination. The study also presents barriers and solutions identified through literature review and qualitative research, along with strategies to enhance professionals' knowledge, improve reachability, promote adherence, achieve vaccination coverage, and evaluate interventions. The study concludes by recommending strategies such as proximity, provider training, a migrant-sensitive approach, and data collection to improve vaccination outcomes for NAMs.Conclusion: Ensuring equitable access to healthcare services, including vaccination, is crucial not only from a humanitarian perspective but also for the overall public health of these countries.